Genomic characterisation of Escherichia coli isolated from poultry at retail through Sink Surveillance in Dhaka, Bangladesh reveals high levels of multi-drug resistance - Davies, Alistair R.; Chisnall, Thomas; Akter, Shamima; Afrad, Md. Mohibul Hassan; Sadekuzzaman, Mohammad; Badhy, Shukes Chandra; Hasan, Md. Zakiul; Rahman, Md. Taifur; Smith, Richard P.; Card, Roderick M.; Brum, Eric; Chowdhury, Md. Golam Azam (Frontiers in Microbiology, 2024)
The surveillance of antimicrobial resistance (AMR) in commensal Escherichia coli from livestock at slaughter is widely employed to assess the potential for risk to humans. There is currently a limited understanding of AMR in Bangladesh poultry at retail in live bird markets, with studies focussing solely on phenotypic characterisation of resistance. To address this evidence gap we performed antimicrobial susceptibility testing and whole genome sequencing on E. coli obtained from chickens from live bird markets in Dhaka in 2018 (n=38) and 2020 (n=45). E. coli were isolated from caeca samples following ISO guidelines and sequenced using short and long read methods. Multidrug resistance was extremely common (n=77) and there was excellent concordance between AMR phenotype and the presence of corresponding AMR genes or mutations. There was considerable genomic diversity, with 43 different sequence types detected. Public health considerations included the high occurrence of resistance to ciprofloxacin (n=75) associated with plasmid-residing qnrS or mutations in the gyrA and parC chromosomal genes; and the detection of a tigecycline resistant isolate harbouring tet(X4) on an IncHI1A/B-IncFIA mosaic plasmid. Thirty-nine isolates were resistant to azithromycin and harboured mphA, with a significant increase in the incidence of resistance between 2018 and 2020. Although azithromycin is banned for veterinary use in Bangladesh it remains an important treatment option for humans. Interestingly, mphA confers high-level resistance to azithromycin and erythromycin, and the latter is commonly used on poultry farms in Bangladesh. Seven isolates were colistin resistant and carried mcr1. For two isolates hybrid assemblies revealed that mcr1 resided on a highly conserved IncHI2 plasmid that had 93% nucleotide identity to a plasmid from the published genome of an E. coli isolate of Bangladeshi human origin. Six isolates had resistance to third generation cephalosporins, associated with plasmid-residing blaCTX-M-55, blaCTX-M-65, or blaDHA-1. By employing phenotypic and genomic approaches for AMR surveillance we have provided new insights into the potential for One Health AMR linkages in Bangladesh. Employing similar approaches in human and environmental sectors will help inform the One Health approach to addressing AMR, and generate evidence to support mitigation measures such as improved antimicrobial stewardship.